Actoral Images in Theatre Rehearsals: Possible Intersections between ‘Anachronism’ and Stage Performance - Vaccalluzzo, Victoria (2026)
The following paper proposes a revision of the scenic practice of theatrical representation during rehearsals in light of Didi-Huberman’s contributions regarding the concepts of «anachronism» and «image-malice». In Confronting Images: Questioning the Ends of a Certain History of Art (2011), the author offers a critique of the classical conception of history in teleological terms. He positions anachronism as a key lens for reading the complex and chaotic temporalities present within images. This article builds upon these premises to analyze the anachronistic dimension of acting practice in theatrical rehearsals, understood as a performative generation in action. Additionally, it draws on reflections by Victoria Pérez Royo (2016), who—drawing from Didi-Huberman—studies the Benjaminian “dialectical image” to consider this notion in relation to scenic practices. Pérez Royo’s contributions regarding the image drive us toward the following question: In what way can we investigate the survival (Nachleben) of images within the creative practice of acting? The idea of bringing this concept of the image closer to the performing arts, as the author proposes, proves useful for interrogating the study of corporality—the materiality of acting praxis—from that perspective.